Those Glass Chains that Bind You: How British Muslim Women Professionals Experience Career, Faith and Family. (28th October 2019) - Arifeen, Shehla R.; Gatrell, Caroline
Abstract: This paper contributes to gender and diversity research through proposing a new theoretical construct: glass chains. We develop 'glass chains' as a metaphor to illuminate how highly educated British Pakistani Muslim women professionals in the UK negotiate a fine balance between faith, family and personal ambition. Using a qualitative approach, we highlight tensions between religious and familial guidance within Islam, and workplace practices. Drawing upon the construct of 'glass chains', we articulate how 37 British Pakistani Muslim career women felt bound, by invisible glass chains, to the tenets of their faith. We show how the pull of glass chains obliged these women to resist certain career‐advancing opportunities. In so doing, we borrow from French philosopher Michel Foucault ideas about self‐oriented moral codes, engaging with his arguments that individuals may prioritize, over other obligations, the ties (or glass chains) which bind them to personal value sets in order that they may become 'ethical selves'. While previous glass metaphors highlight barriers to female progression from external and structural angles, 'glass chains' are, by contrast, concerned with the potential for internal and personal constraints on women's ambitions. The metaphor 'glass chains' may be extended to enhance understanding of career constraints among other workers.